2013
DOI: 10.1017/jns.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Faster growth rate inad libitum-fed cats: a risk factor predicting the likelihood of becoming overweight during adulthood

Abstract: In human subjects, the risk of becoming overweight (OW) in adulthood is largely determined early in childhood. However, early-life factors have not been considered for feline obesity. A total of eighty colony cats, fed ad libitum, were studied; various breeds, ages and sex were included, with thirty-six (45 %) being OW and forty-four (55 %) being of ideal weight (IW). The effects of various factors (including age, sex, neuter status, breed (pure v. mixed), mean daily food intake (FI), housing status (indoor wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…These previous studies have all been cross-sectional in design, resulting in uncertainty over the causal direction of associations observed between putative risk factors and obesity. The first longitudinal study (to the authors' knowledge) to investigate risk factors for feline obesity was conducted on a small scale (80 cats) using colony cats rather than pet cats (Serisier et al, 2013). The authors found that a higher percentage change in body weight between 3 and 12 months (as well as male sex, in agreement with previous studies) was significantly associated with increased risk of obesity in adulthood.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…These previous studies have all been cross-sectional in design, resulting in uncertainty over the causal direction of associations observed between putative risk factors and obesity. The first longitudinal study (to the authors' knowledge) to investigate risk factors for feline obesity was conducted on a small scale (80 cats) using colony cats rather than pet cats (Serisier et al, 2013). The authors found that a higher percentage change in body weight between 3 and 12 months (as well as male sex, in agreement with previous studies) was significantly associated with increased risk of obesity in adulthood.…”
Section: Introductionsupporting
confidence: 75%
“…This, along with the evidence from Serisier et al (2013) that growth rate in kittenhood was associated with obesity in adulthood, suggests that factors which increase a cat's risk of obesity occur early in life. This in turn is supported by the literature on early-life critical periods in childhood for the development of human obesity (Dietz, 1994).…”
Section: Introductionmentioning
confidence: 90%
“…In a study of body weight during growth and adulthood in cats held in a colony, overweight adult cats were heavier at 1 year of age than cats that remained lean for their adult lives (Serisier, Feugier, Venet, Biourge, & German, ). In a small subset of cats evaluated, there was no significant difference between the two groups of cats at 3 months, although body weight at 3 months was a significant covariate in a model of weight change between 3 and 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Excess weight is a major health concern in cats ( 1 ) , with studies suggesting that up to 52 % of the adult cat population are overweight or obese ( 2 – 5 ) . Overweight is associated with an increased risk of mortality, predisposes individuals to chronic metabolic disorders, such as diabetes mellitus and hepatic lipidosis, and reduces quality of life through chronic diseases, such as osteoarthritis ( 6 ) .…”
mentioning
confidence: 99%
“…This is especially important, as evidence indicates that risk factors for being overweight as an adult include the rate of growth in ad libitum -fed cats ( 5 ) , feeding a dry diet and restricted exercise at age 12·5–13 months ( 9 ) . Furthermore, neutering, often carried out in the first year of life, is also a major significant risk factor for obesity.…”
mentioning
confidence: 99%